Current challenges in optimizing systemic therapy for patients with pancreatic cancer: expert perspectives from the Australasian Gastrointestinal Trials Group (AGITG) with invited international faculty. Issue 10 (3rd October 2017) - Segelov, Eva; Lordick, Florian; Goldstein, David; Chantrill, Lorraine A.; Croagh, Daniel; Lawrence, Ben; Arnold, Dirk; Chau, Ian; Obermannova, Radka; Price, Timothy Jay
ABSTRACT: Introduction : Despite recent progress, the outlook for most patients with pancreatic cancer remains poor. There is variation in how patients are managed globally due to differing interpretations of the evidence, partly because studies in this disease are challenging to undertake. This article collates the evidence upon which current best practice is based and offers an expert opinion from an international faculty on how latest developments should influence current treatment paradigms. Areas covered : Optimal chemotherapy for first and subsequent lines of therapy; optimal management of locally advanced, non-metastatic cancer including the role of neoadjuvant chemo(radio)therapy, current evidence for adjuvant chemotherapy, major advances in pancreatic cancer genomics and challenges in supportive care particularly relevant to patients with pancreatic cancer. For each section, literature was reviewed by comprehensive search techniques, including clinical trial websites and abstracts from international cancer meetings. Expert commentary : For each section, a commentary is provided. Overall the challenges identified were: difficulties in diagnosing pancreatic cancer early, challenges for performing randomised clinical trials in all stages of the disease, some progress in systemic therapy with new agents and in identifying molecular subtypes that may be clinically relevant and move towards personalized therapy, but still, pancreatic cancer remains a very poor prognosis cancer with significant palliative care needs.